A new tilted strips external thermal insulation composite system (TiS-ETICS): Description and performance assessment through thermal and energy simulation for a residential building - Margarida Almeida (2021)
This work presents a new concept of facades coated with machined ETIC boards displaying tilted strips. Strips with upwards tilt have a high total solar reflectance (TSR) paint, to maximize the solar radiation reflection during the summer period. Strips tilted downwards have a low TSR paint, to maximize the solar absorption during wintertime. Parameters that characterize this new tilted strips ETIC system (TiS-ETICS) were optimized for four different locations: Porto, Sao Paulo, Los Angeles, and Sydney. The indoor temperature, in the free-floating mode, and the energy demand needed over the year, in conditioned mode, were both assessed through building simulation. The use of TiS-ETICS, compared to pristine facades, always led to a positive impact on performance. In free-floating mode, with the new system, indoor temperatures dropped in summer and increased in winter. In conditioned mode, annual energy savings between 10.8% (in Porto) and 32.3% (Sao Paulo) were obtained.